Caracterización fisicoquímica y espectrométrica del aceite de tortuga Geochelone denticulata Linnaeus (motelo) comercializado en el mercado Belén, Loreto - Reyna Rengifo, Bella Luz Estrella (2025)
The medicinal use of fauna is an ancestral practice in that the inhabitants use part of them or their derivatives such as oils, to alleviate ailments or other conditions, in the Amazon Geochelone denticulata oil is used for pulmonary, cardiovascular, and anti-wrinkle conditions. The study's objective was to characterize by measuring its physicochemical properties and by chromatographic analysis the oil of G. denticulata that is commercialized in the Belen, Loreto market. The oil was obtained from turtle fat marketed in informal stalls near the Belén market in a water bath. The physicochemical parameters were estimated using the methods of the analysis indicated in the United States pharmacopeia (USP-40) for oils and fats, and a gas chromatograph coupled to a mass spectrometer was used to identify the components. The physicochemical characteristics determined were acidity 1.1mg KOH/g oil, peroxides 3.4meq O2/kg oil, iodine 9.60g I2 /100g oil, and saponification 245.0mg KOH/g oil. The chromatographic analysis identified 12 components, the most abundant of which were oleic acid 54.78%, palmitic acid 19.74%, palmitoleic acid 7.59%, and stearic acid 5.49%. The presence of oleic acid as a major component whose characteristic is anti-inflammatory and skin rehydrating corroborates the ethnomedicinal use given to this oil by the Indigenous peoples of the Amazon.